The Decision to Emigrate in Six MENA Countries: The Role of Post-Revolutionary Stress - Ali Fakih; Malak El Baba (Institute of Labor Economics (IZA), 2023)
This paper studies the determinants of emigration from six Middle East and North Africa (MENA) countries in light of the Arab Spring of 2011. The aim is to determine if the economically depressing events which occurred as a result of the Arab Spring, resulted in brain drain for many countries. The paper's analysis is conducted using the Arab Transformation Project dataset of the year 2014 by employing an ordered probit model. The main conclusion of the paper is that sentiments of unhappiness appear to be the main determinant of the decision to emigrate. Other post-revolutionary feelings include lack of trust and political and democratic discontent, which highly encourage emigration decisions. In addition, socio-economic factors, such as being young, being male, and being highly educated are all contributing factors to the willingness to emigrate. However, married individuals are less likely to consider emigration.
Keywords: C25; J60; O15; 330; Arab Spring; emigration; unhappiness; attitude